ANALISIS BAHAN KERAMIK PRIFILIT SEBAGAI PENGGANTI LOGAM PADA KETEL RICE COOKER - Purnomo, Agung; Rifaii, Rizal Aditya; Puspita, Dian (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research aims (1) to determine the components of the rice cooker, (2) to determine the distribution of heat in the rice cooker with aluminium pans and ceramic pans, (3) to determine the quality and taste of rice cooked by a rice cooker with an aluminium pan and ceramic pan, (4) to determine the metal content of the rice cooker with an aluminium pan and ceramic pan. The research is quantitative and qualitative in nature. The quantitative research is conducted by measuring the heat on the rice rice cooker with an aluminium pan and ceramic pan that can be made by their physical distribution system. The second is chemical metal content of rice cooker with an aluminium pan and ceramic pan. The qualitative research focuses on the quality and flavor of rice with an organoleptic test. The result of this study is the product of a rice cooker from ceramic pans from Pagar Jurang, Klaten. To support the physical processes of the rice cooker, the study needs to detect the components in the rice cooker itself. Because the process of cooking rice by using a rice cooker cannot be separated from the electronic system. The research continues on finding out the difference in the cooking process by using ceramic pans and aluminium pans. Cooking rice within two hours has different detailed processes and different rice. The process uses a ceramic pan has increasing temperature which is longer than that using an aluminum one. Basically, cooking uses a ceramic pan is successful but needs further research to produce good quality of rice faster. The results of the SSA test show that ceramic contains approximately 10% of aluminum that supports this behavior in the conductivity of the ceramic itself. If compared with the aluminum pan, aluminum which contains about 83% is certainly bigger than a ceramic pan and make a rice cooker with a ceramic pan environmentally friendlier than the aluminium pan. Based on thenorganoleptic test, the rice cooked by using the ceramic pan is fresher and more distinctive.